Pre-Pregnancy Provegetarian Food Pattern and the Risk of Developing Gestational Diabetes Mellitus: The Seguimiento Universidad de Navarra (SUN) Cohort Study - Vanessa Bullón-Vela; Ainara Martínez-Tabar; Maddi Etxezarreta-Uranga; Miguel Ángel Martínez-González; Francisco Javier Basterra-Gortari; Maira Bes-Rastrollo (Medicina)
Background and Objectives: Gestational diabetes mellitus (GDM) is one of the most common medical conditions in pregnancy, with adverse effects on maternal and neonatal outcomes. Evidence suggests a beneficial effect of plant-based dietary patterns, rich in foods derived from plant sources and low in animal foods, on type 2 diabetes; however, their effects on GDM remain unclear. We aimed to investigate the association between pre-pregnancy provegetarian food patterns and the incidence of GDM in a Spanish cohort. Materials and Methods: This subsample of the Seguimiento Universidad de Navarra (SUN) cohort analyzed 3589 Spanish university graduate pregnant women with a mean (standard deviation) age of 28 (±4.3) who were initially free of pre-existing diabetes at baseline. Dietary food consumption was evaluated through a validated, 136-item semi-quantitative food frequency questionnaire. The pre-pregnancy provegetarian food pattern was obtained by assigning positive scores to plant-based food groups and reverse scores to animal food groups. Energy-adjusted quintiles were applied to allocate points to construct the provegetarian food pattern, ranging from 12 to 60 points. Logistic regression models were performed to estimate the odds ratios (OR) of GDM across quintiles of a pre-pregnancy provegetarian food pattern, using the lowest quintile as the reference category. Results: We identified 178 incidence cases of GDM. Women in the highest quintile (Q5) of provegetarian food pattern before pregnancy exhibited a 42% relative reduction in the odds of GDM [adjusted OR (95% CI) Q5 vs. Q1: 0.58 (0.35, 0.97); p-trend = 0.109]. Higher consumption of meat and dairy before pregnancy was associated with a significantly increased risk of GDM [adjusted OR (95% CI) Q5 vs. Q1: 1.94 (1.19, 3.16); p-trend = 0.005] and [adjusted OR (95% CI) Q5 vs. Q1: 1.77 (1.07, 2.94); p-trend = 0.082], respectively. Conclusions: Higher pre-pregnancy consumption of a provegetarian food pattern was associated with a lower risk of developing GDM in Spanish women. Further studies are needed to confirm these findings.